Effect of blending sewage sludge with coal on combustion and ash slagging behavior. Issue 51 (19th September 2019) - Guo, Shuai; Yang, Qiyao; Liang, Honglin; Che, Deyong; Liu, Hongpeng; Sun, Baizhong
Abstract : Blending sewage sludge (SS) with Zhundong coal (ZDC) for combustion in coal-fired power plants is a recent approach that can alleviate the shortage of high-quality coal resources and achieve the harmless treatment of SS, while also having a significant influence on combustion and ash slagging. Abstract : Blending sewage sludge (SS) with Zhundong coal (ZDC) for combustion in coal-fired power plants is a recent approach that can alleviate the shortage of high-quality coal resources and achieve the harmless treatment of SS, while also having a significant influence on combustion and ash slagging. Due to the high content of alkali and alkaline earth metals (AAEMs) in ZDC, its combustion ash has a strong likelihood of slagging. This study aims to investigate the effect of blending SS with ZDC on combustion and ash slagging. Thermogravimetry (TG) results indicate that blending with SS could lower the ignition and burnout temperatures of ZDC. With an increase in the ratio of sludge, the comprehensive combustion index ( S ) first increases and then decreases, showing that blending SS with ZDC in an appropriate proportion could improve the overall combustion. Through the analysis of the interaction, it is confirmed that SS and ZDC could complement each other during co-combustion due to their different components. X-ray fluorescence (XRF) was used to test the ash components of different blending ratios (10–30%) and combustion temperatures (800–1100 °C). Slagging indices including alkali acid ratio ( B / A ), silicon ratio ( G ), and silica–alumina ratio (SiO2 /Al2 O3 ) were also calculated. The results suggest that the slagging behavior of ZDC is greatly reduced even if the blending ratio is only 10%. However, with an increase in the blending ratio, the effect on slagging gradually weakens. Considering the dual influence of SS blending on combustion and slagging, this study assumes the optimal blending ratio of 20%. Influenced by the components of the combustion ash, B / A and SiO2 /Al2 O3 are more suitable for evaluating the slagging tendency of ash; however, there is great deviation in the results for G . This research is beneficial to coal-fired power plants for the selection of operation parameters during co-combustion with SS.